“Not that I lov’d Fleas less, but that I lov’d England more,”: Entertainment in Kingston, 1816-1837 - Beaulieu, Michel (Ontario History)

(untitled) (The Ontario Historical Society, 2010)
Upper Canadians were avid participants in “entertainment.” They took part as spectators and participants in a wide variety of activities that, on one level, provided an opportunity for leisure and social interaction. However, for historians, the type and dialogue surrounding them also played another, somewhat more significant, role. As this paper argues, the many forms of public and private amusement available in Kingston, Ontario, between 1815 and 1837 provide a barometer of the social and political atmosphere of the town.